PENGGUNAAN MEDIA RITATOON PADA PEMBELAJARAN RAGAM HIAS UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS V SD NEGERI 54 BANDA ACEH - Putri Aprillia Zuhra; Aida Fitri; Mislinawati (STKIP Subang, 2026)
The low creativity of students in art education, particularly in the decorative arts material, is caused by the lack of innovative learning media, which tends to make students passive and less able to develop ideas in their artwork. One of the innovative learning media that teachers can implement is Ritatoon media. This study aims to determine teacher and student activities, as well as the improvement of students' creativity in learning decorative arts using Ritatoon media in class V A of SD Negeri 54 Banda Aceh. This study employed a qualitative approach using Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection phases. The subjects of this study were 31 students of class V A at SD Negeri 54 Banda Aceh. Data collection techniques were carried out through observation, performance tests, and documentation. The data were analyzed using quantitative and descriptive qualitative methods. The results showed that the use of Ritatoon media could improve students' creativity in learning decorative arts. Teacher activity increased from 85% in cycle I to 100% in cycle II, falling into the excellent category. Student activity increased from 66% in cycle I, categorized as good, to 100% in cycle II, categorized as excellent. The improvement in student creativity in cycle I obtained an average score of 56.04, which then increased to 85.68 in cycle II. Thus, it can be concluded that the use of Ritatoon media in decorative arts learning can improve the creativity of fifth-grade students at SD Negeri 54 Banda Aceh.